Strategi Penguatan Literasi dan Numerasi Siswa melalui Program Asistensi Mengajar di SMP Negeri 4 Mauliru - Andrew Setiawan Ratu Djingi; Jesi Tenga Lunga; Merni Harabi Loda; Narwasti Dehu Mboru; Yoin Meissy Matulessy; Anita Tamu Ina (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Teaching Assistance is part of the MBKM (Merdeka Belajar Kampus Merdeka) program which aims to improve students’ literacy and numeracy skills and provide opportunities for students to learn and develop themselves. One of the target schools for this program is SMP Negeri 4 Mauliru. This program includes various strategies, including optimizing reading corners equipped with picture illustrations to attract students’ interest as well as casual reading activities aimed at improving reading habits. Apart from that, this program also involves distributing multiplication brochures to strengthen students’ understanding of numeracy as well as making literacy and numeracy posters with the aim of providing a deeper understanding while strengthening educational messages about the importance of literacy and numeracy. The main aim of this program is to improve students’ literacy and numeracy skills, as well as support the development of basic abilities and create a fun learning environment. The results show that this program has a positive impact by increasing literacy and numeracy skills, as well as students’ learning motivation and interest in reading.